Consumer Behaviour and Moderating Effect of Frequency of Visit in Relation to Atmospheric Cues: An Experimental Study - Jha, Shalini; Singh, Bharti (Indian Journal of Marketing, 2014)
Today, the retailers are striving hard to provide excellent customer experience because it is vital for their sustainability. Researchers and retailers have identified the importance of atmospheric in creating a good customer experience. The present study is based on the experimental study conducted in a real retail setting. Two atmospheric cues - background music and affability of the salesperson were considered for the experimental study in a real retail setting. The study shows the presence of moderating effect of frequency of visit to the store on the perception only for affability of salesperson and not on background music. Moderating effect of frequency of visit was not found on perception of merchandise quality and overall environment in the presence of atmospheric stimuli selected for the experimental study. But as far as emotion and behavior of shoppers are concerned, frequency of visit did have a moderating effect on the same. The study suggests that the retailers should provide novelty in atmospheric for frequent visitors to increase store patronage.